PENGARUH KOMISARIS INDEPENDEN, KOMITE AUDIT,RISK MANAGEMENT COMMITTEE DAN REPUTASI AUDITOR TERHADAP ENTERPRISE RISK MANAGEMENTPADA PERUSAHAAN BUMN DI INDONESIA - M., RISWAN (Jurnal Akuntansi AKUNESA, 2015)
This study aims to analyze the influence of independent commissioners, audit committee, risk management committee, and auditor reputation on the disclosure of enterprise risk management in state-owned companies at Indonesia. The study population is all state-owned companies registered in the ministry of state-owned enterprises 2011-2014 period by using purposive sampling method. The research method uses multiple linear analysis. The results show independent commissioners and audit committee has no effect on the disclosure of ERM while risk management committee, and the auditor's reputation effect on disclosure of ERMKeywords: independent commissioners, audit committee, risk management committee, the auditor's reputation, enterprise risk management